Religion, nationalism, and European integration: introduction - Koenig, Matthias; Knöbl, Wolfgang (Religion and national identities in an enlarged Europe, 2015)
Who would have thought that claims of secular humanist parents in Northern Italy to have crucifixes removed from classrooms in public schools would result in Europe-wide controversies over the legitimacy of religious signs as symbols of national identity? The European Court of Human Rights in Strasbourg — where these claims were adjudicated after exhaustion of domestic remedies — initially argued, in 2009, that the obligatory display of crucifixes in public schools violated both the state’s duty to neutrality and parents’ and children’s rights to freedom of religion. Prompting broad-scale counter-mobilization by various member states (mostly Orthodox), Catholic lawyer associations, and Protestant nongovernmental organizations, this chamber judgment in what is known as the Lautsi v Italy case was overturned by the same court’s Grand Chamber in 2011, now arguing that the crucifix was a ‘passive’ religious symbol to which the Italian government could legitimately give ‘preponderant visibility’ (for discussion, see Tempermann 2012). Religion, or so the Lautsi saga suggests, has become a highly visible, if contested, marker of national identity in seemingly secular Europe.